An inscription of Ashurnasipral II from the Ištar-Šarrat-Niphi temple at Nimrud - Yaseen Al-Juboori, Ali (Iraq, 2018)
An inscription of Ashurnasirpal II (r.883–859 b.c.) was found in the temple of Ištar-Šarrat-niphi at Kalhu (Nimrud) in 2001, during the excavations of the Nineveh inspectorate expedition (State Board of Antiquities and Heritage). The preserved text duplicates RIMA 2 A.0.101.1 i 18–117. This article presents a transliteration, a table of variants, and a translation into Arabic.